KINERJA KECAMATAN BUKITRAYA SEBAGAI KECAMATAN TERBAIK DI KOTA PEKANBARU - Ivan Dinata; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Subdistrict government is a set of working unit bellow regency government that leaded by a subdistrict head as coordinator of common government activities implementation and to do authority that gived to subdistrict and other orders. Subdistrict activities must always monitored by regency government. Pekanbaru government does subdistrict performance evaluation that the result is fungtioned to recommendation the decision making in reparation services and development of subdistrict for success of developing program of Pekanbaru City. Some contents that evaluate in subdistrict performance evaluation program, but generally Subdistrict of Bukitraya gets first rank subdistrict performance evaluation in 2014. This research is intended to understand how Subdistrict of Bukitraya as the best Subdistrict in Pekanbaru City, indirectly knowing factors that influence activity of Bukitraya Subdistrict that focused on carry out service to public. Concept of theory that researcher uses is performance and services. This research is using qualitative research method and evaluating data with descriptive method. Collectiong data with interview technique, observation, documentation and library research. The Result of this research showing that Subdistrict of Bukitraya performance in carry out service to public has done well enough, because of services quality, productivity, responsivity, responsibility and accountability of service activity in Subdistrict of Bukitraya has contributed to public of Bukitraya. Factors that influence Pekanbaru City, Subdistrict of Bukitraya performance in doing services to public influenced by work motivation of officer, human resource, and also infrastructure. Keywords: performance, service, subdistricts of Bukitraya